Regulation and improvement of filler wetting behavior and brazed joint performance based on microfluidics. (March 2023) - Chen, Haiyan; Kong, Xiangwei; Zhao, Shuai; Nai, Xin; Wang, Qian; Li, Wenya
Abstract: Improving the accuracy of brazing has important scientific significance and engineering value to promote its application in the field of high-precision welding. In this study, microfluidics was used to effectively control the wetting behavior of liquid filler during brazing, thereby promoting the improvement of joint performance. A regular triangular prism-shaped surface microstructure was designed as the microfluidic system and fabricated on the Ti3 SiC2 ceramic surface by vapour deposition and fine laser etching. The wetting behavior of liquid filler is synergistically regulated by the ceramic phase region that inhibits wetting and the metal phase region that promotes wetting. The wetting driving force and the final wetting angle of the liquid filler on the microstructure surface during brazing were deduced by analytical calculation. Wetting tests were carried out using two kinds of brazing fillers with large differences in wettability, and the results show that the triangular prism-shaped microfluidic system can effectively promote the wetting process, which is in good agreement with the theoretical calculations. Moreover, under the same brazing parameters, the shear strength of brazed joints with microfluidic structures is 15.4% higher than that without microfluidic structures. Graphical Abstract: ga1 Highlights: A regular surface microstructure was designed as the microfluidic system. Wetting angles of the liquid filler were greatly promoted by microfluidics. The shear strength of the joint with microfluidics was increased by 15%.